High-viscosity nano-coating copper current collector and preparation method thereof

By depositing a copper halogenated film on the copper current collector surface and modifying a polyacrylic binder, the problem of degradation of the bonding performance of the nanocoated copper current collector in the prior art is solved, and the peel strength and battery service life are significantly improved.

CN119742370AActive Publication Date: 2025-04-01JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411909085.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing nanocoated copper current collectors are susceptible to water during the preparation process, resulting in a decrease in adhesive performance and weakening of peel strength, which affects the rate performance and service life of lithium-ion batteries.

Method used

The surface roughness is increased by depositing a copper halogenated film on the surface of the copper current collector; at the same time, a polyacrylic binder is modified to enhance the bonding ability, and water resistance and slip resistance are improved by cross-linking and addition of anchoring agents.

Benefits of technology

It significantly improves the bonding performance between the nanocoating and the negative electrode material, enhances the peel strength, maintains the conductivity of the current collector, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205159510000121
    Figure BDA0005205159510000121
Patent Text Reader

Abstract

The invention relates to the technical field of copper current collectors, and particularly discloses a high-viscosity nano-coating copper current collector and a preparation method thereof.A conductive agent, a binder, a cross-linking agent and an anchoring agent are mixed and then coated on the copper current collector, the method is simple, the manufacturing cost is low, the stripping performance of a negative electrode material and the current collector is remarkably improved, and the service life of the current collector is prolonged. The prepared high-viscosity nano-coated copper current collector has relatively high water resistance, peel strength, conductivity and safety, the peel strength of the high-viscosity nano-coated copper current collector is further enhanced after rolling, and further processing of an electrode material is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper current collectors, in particular to a high-adhesion nano-coating copper current collector and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have gradually begun to be used in consumer electronics, electric vehicles and other fields. The market has also put forward higher requirements for the energy density, cycle life, and safety of lithium-ion batteries. The current collector is an important component of lithium-ion batteries, which plays the role of collecting electrons, supporting active substances, and stabilizing the battery structure. In the negative electrode system, the current collector conductive primer technology can effectively improve the battery's rate performance, increase the adhesion between the electrode material and the current collector, and extend the battery life.

[0003] In the prior art, copper foil is usually used as the negative electrode current collector material for lithium-ion batteries. For the negative electrode, the negative electrode material is mostly an aqueous system. The nano-coated copper current collector is required to have good water resistance, electrolyte performance and strong bonding performance during the preparation process. The commonly used nano-coating is an aqueous binder, which will cause partial dissolution and slippage of the nano-coating during the coating of the negative electrode material, affecting the stripping performance of the negative electrode material and the current collector; on the other hand, this partial impact will be amplified again in the rolling process after the coating of the negative electrode material, aggravating the slippage of the nano-coating. This is also the reason why the stripping strength of the nano-coated copper current collector after rolling is usually lower than that before rolling in the prior art, thereby affecting the overall effect of the electrode. Summary of the invention

[0004] The purpose of the present invention is to provide a high-adhesion nano-coated copper current collector and a preparation method thereof, which reduces the ability of water to penetrate the coating film by increasing the water resistance of the nano-coating and improving the anti-slip ability of the nano-coating, improves the adhesion between the nano-coating and the negative electrode material without affecting the overall conductivity of the current collector, and solves the problem that the existing adhesive affects the peeling strength between the negative electrode material and the current collector.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A high-adhesion nano-coated copper current collector comprises a copper current collector and a nano-coating coated on the surface of the copper current collector. The dosage of each component in the nano-coating is: 6 to 22 parts of a conductive agent, 0.05 to 4 parts of an anchoring agent, 0.5 to 1.5 parts of a modified polyacrylic acid binder, and 0.01 to 0.1 parts of a cross-linking agent.

[0007] As a limitation of the present invention, the conductive agent includes a conductive agent A and a conductive agent B, the conductive agent A is at least one of conductive carbon black and carbon nanotubes, the conductive agent B is at least one of conductive graphite and graphene, the particle size of the conductive agent B is 1 to 2 μm, and the mass ratio of the conductive agent A to the conductive agent B is (5 to 10):1.

[0008] As a limitation of the present invention, the crosslinking agent is at least one of isocyanate, aziridine type curing agent and epoxy type curing crosslinking agent; the anchoring agent is at least one of alumina ceramic particles and boehmite.

[0009] A method for preparing a high-adhesion nano-coated copper current collector, the preparation method comprising:

[0010] Conductive agent A, conductive agent B, anchoring agent, modified polyacrylic acid binder and deionized water are mixed, a crosslinking agent is added, and the mixture is stirred evenly to obtain a nano coating slurry, and the nano coating slurry is coated on a copper current collector to obtain a high-adhesion nano coating copper current collector.

[0011] As a limitation of the present invention, the specific preparation steps of the modified polyacrylic acid binder are:

[0012] Mix sodium hydroxide and deionized water, stir evenly to obtain a sodium hydroxide solution, mix acrylic acid with the sodium hydroxide solution at 0-10°C to obtain a sodium acrylate solution, add acrylamide to the sodium acrylate solution, stir evenly to obtain a sodium acrylate-acrylamide mixed solution, mix methyl allyl polyoxyethylene ether and deionized water, stir evenly to completely dissolve them, add the sodium acrylate-acrylamide mixed solution, acrylonitrile and ammonium persulfate under nitrogen protection, react at 65-75°C and 250-350rpm for 8-10h, cool after the reaction is completed, freeze-dry, wash with anhydrous ethanol, filter and obtain a modified polyacrylic acid binder.

[0013] As a limitation of the present invention, the copper current collector is a copper bromide surface-modified copper current collector, and the preparation method is:

[0014] The copper current collector is washed with ethanol and deionized water to remove dust and impurities on the surface, and dried at room temperature to obtain a pretreated copper current collector. Copper sulfate pentahydrate and deionized water are mixed and stirred evenly. Dodecyltrimethylammonium bromide is added and ultrasonically dispersed to form a mixed solution. The pretreated copper current collector is placed in the mixed solution and immersed at room temperature for 5 to 20 minutes. After the immersion is completed, it is taken out, washed with deionized water, and dried to obtain a copper current collector with a cuprous bromide surface modification.

[0015] As a limitation of the present invention, the copper current collector is a copper current collector surface-modified with cuprous iodide, and the preparation method is:

[0016] The copper current collector is washed with ethanol and deionized water to remove dust and impurities on the surface, and dried at room temperature to obtain a pretreated copper current collector. Copper sulfate pentahydrate and deionized water are mixed and stirred evenly. 1-butyl-3-methylimidazole iodide is added and ultrasonically dispersed to form a mixed solution. The pretreated copper current collector is placed in the mixed solution and immersed at room temperature for 5 to 20 minutes. After the immersion is completed, it is taken out, washed with deionized water, and dried to obtain a cuprous iodide surface-modified current collector.

[0017] As a limitation of the present invention, the modified polyacrylic acid binder is a polydopamine-modified polyacrylic acid binder, and the preparation method is:

[0018] Dopamine is mixed with tris(hydroxymethyl)aminomethane hydrochloric acid buffer solution, and stirred at room temperature for 6 to 10 hours to obtain a polydopamine solution. The polydopamine solution and a modified polyacrylic acid binder are evenly mixed to obtain a polydopamine-modified polyacrylic acid binder.

[0019] The invention discloses an application of a high-adhesion nano-coating current collector in a negative electrode material of a lithium-ion battery.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] By depositing a layer of cuprous halide film on the surface of the copper current collector, the roughness of the surface of the copper current collector is increased, and the bonding force between the binder and the copper current collector is enhanced.

[0022] By modifying the acrylic binder so that it has active groups such as carboxyl and amide groups or has a quinone structure and an amine group, the dispersibility and bonding ability of the binder can be improved. In addition, the cyanide and amide groups can promote the conduction of ions or electrons and improve the rate performance of the battery, while the polyoxyethylene ether chain segments can provide the binder with elasticity and ionic conductivity, thereby preventing the pole pieces or active materials from falling off during deformation.

[0023] The water resistance and compaction resistance of the traditional nano-coated copper current collector are improved by cross-linking and adding anchoring agents. It has high water resistance, peel strength, high conductivity and safety, low production cost and simple method. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Conductive carbon black (50nm) and conductive graphite (2μm) were provided by Sigma-Aldrich (Shanghai), copper current collector (6μm) was provided by Far East Copper Foil, methyl allyl polyoxyethylene ether (molecular weight 2400) and aziridine type crosslinker (Sac100, 1.08kg / L) were provided by Jinjinle Chemical, and polyacrylic acid (molecular weight 2000) and tris(hydroxymethyl)aminomethane hydrochloric acid buffer (pH=8) were provided by Shanghai Eon Chemical.

[0026] Embodiment 1: A method for preparing a high-adhesion nano-coated copper current collector, specifically:

[0027] 10kg of conductive carbon black, 1kg of conductive graphite, 1kg of alumina, 40kg of 25wt% modified polyacrylic acid binder and 168kg of deionized water were mixed, 0.1kg of aziridine type crosslinking agent was added, and stirred evenly to obtain a nano-coating slurry. The obtained nano-coating slurry was coated on a 6μm copper current collector with a coating thickness of 1μm to obtain a high-adhesion nano-coating copper current collector.

[0028] Wherein, the preparation method of the modified acrylic acid adhesive is:

[0029] 8.5 kg of sodium hydroxide and 42.5 kg of deionized water were mixed and stirred to obtain a sodium hydroxide solution. At 5°C, 15 kg of acrylic acid was mixed with the sodium hydroxide solution to obtain a sodium acrylate solution. 4 kg of acrylamide was added to the sodium acrylate solution and stirred to obtain a sodium acrylate-acrylamide mixed solution. 0.75 kg of methyl allyl polyoxyethylene ether and 20 kg of deionized water were mixed and stirred to completely dissolve. Under nitrogen protection, the sodium acrylate-acrylamide mixed solution, 6 kg of acrylonitrile and 1.25 kg of ammonium persulfate were added, and the mixture was reacted at 70°C and 300 rpm for 9 hours. After the reaction was completed, the mixture was cooled, freeze-dried, washed with anhydrous ethanol, and filtered to obtain a modified acrylic binder. 75 kg of deionized water was added to dissolve the mixture to obtain a 25 wt% modified acrylic binder.

[0030] Embodiment 2: A method for preparing a high-adhesion nano-coated copper current collector, specifically:

[0031] 10kg of conductive carbon black, 2kg of conductive graphite, 1kg of alumina, 40kg of 25wt% modified polyacrylic acid binder and 168kg of deionized water were mixed, 0.1kg of aziridine type crosslinking agent was added, and stirred evenly to obtain a nano-coating slurry. The obtained nano-coating slurry was coated on a 6μm copper current collector with a coating thickness of 1μm to obtain a high-adhesion nano-coating copper current collector.

[0032] Wherein, the preparation method of the modified acrylic acid adhesive is:

[0033] 8.5 kg of sodium hydroxide and 42.5 kg of deionized water were mixed and stirred to obtain a sodium hydroxide solution. At 5°C, 15 kg of acrylic acid was mixed with the sodium hydroxide solution to obtain a sodium acrylate solution. 4 kg of acrylamide was added to the sodium acrylate solution and stirred to obtain a sodium acrylate-acrylamide mixed solution. 0.75 kg of methyl allyl polyoxyethylene ether and 20 kg of deionized water were mixed and stirred to completely dissolve. Under nitrogen protection, the sodium acrylate-acrylamide mixed solution, 6 kg of acrylonitrile and 1.25 kg of ammonium persulfate were added, and the mixture was reacted at 70°C and 300 rpm for 9 hours. After the reaction was completed, the mixture was cooled, freeze-dried, washed with anhydrous ethanol, and filtered to obtain a modified acrylic binder. 75 kg of deionized water was added to dissolve the mixture to obtain a 25 wt% modified acrylic binder.

[0034] Embodiment 3: A method for preparing a high-adhesion nano-coated copper current collector, specifically:

[0035] 10kg of conductive carbon black, 1kg of conductive graphite, 1kg of alumina, 40kg of 25wt% modified polyacrylic acid binder and 168kg of deionized water were mixed, 1kg of aziridine type crosslinking agent was added, and stirred evenly to obtain a nano-coating slurry. The obtained nano-coating slurry was coated on a 6μm copper current collector with a coating thickness of 1μm to obtain a high-adhesion nano-coating copper current collector.

[0036] Wherein, the preparation method of the modified acrylic acid adhesive is:

[0037] 8.5 kg of sodium hydroxide and 42.5 kg of deionized water were mixed and stirred to obtain a sodium hydroxide solution. At 5°C, 15 kg of acrylic acid was mixed with the sodium hydroxide solution to obtain a sodium acrylate solution. 4 kg of acrylamide was added to the sodium acrylate solution and stirred to obtain a sodium acrylate-acrylamide mixed solution. 0.75 kg of methyl allyl polyoxyethylene ether and 20 kg of deionized water were mixed and stirred to completely dissolve. Under nitrogen protection, the sodium acrylate-acrylamide mixed solution, 6 kg of acrylonitrile and 1.25 kg of ammonium persulfate were added, and the mixture was reacted at 70°C and 300 rpm for 9 hours. After the reaction was completed, the mixture was cooled, freeze-dried, washed with anhydrous ethanol, and filtered to obtain a modified acrylic binder. 75 kg of deionized water was added to dissolve the mixture to obtain a 25 wt% modified acrylic binder.

[0038] Embodiment 4: A method for preparing a high-adhesion nano-coated copper current collector, specifically:

[0039] 10kg of conductive carbon black, 1kg of conductive graphite, 1kg of alumina, 40kg of 25wt% modified polyacrylic acid binder and 168kg of deionized water were mixed, 0.1kg of aziridine type crosslinking agent was added, and stirred evenly to obtain a nano coating slurry. The obtained nano coating slurry was coated on a copper bromide surface modified copper current collector with a coating thickness of 1μm, thereby obtaining a high adhesion nano coating copper current collector.

[0040] Wherein, the preparation method of the cuprous bromide surface modified copper current collector is:

[0041] The 6 μm copper current collector was washed with ethanol and deionized water to remove dust and impurities on the surface and dried at room temperature to obtain a pretreated copper current collector.

[0042] 15 kg of copper sulfate pentahydrate and 100 kg of deionized water were mixed and stirred evenly, 0.46 kg of dodecyltrimethylammonium bromide was added, and ultrasonic dispersion was performed to form a mixed solution. The pretreated copper current collector was placed in the mixed solution and immersed at room temperature for 10 minutes. After the immersion was completed, it was taken out, washed with deionized water, and dried to obtain a copper bromide surface-modified copper current collector.

[0043] The preparation method of the modified acrylic acid adhesive is:

[0044] 8.5 kg of sodium hydroxide and 42.5 kg of deionized water were mixed and stirred to obtain a sodium hydroxide solution. At 5°C, 15 kg of acrylic acid was mixed with the sodium hydroxide solution to obtain a sodium acrylate solution. 4 kg of acrylamide was added to the sodium acrylate solution and stirred to obtain a sodium acrylate-acrylamide mixed solution. 0.75 kg of methyl allyl polyoxyethylene ether and 20 kg of deionized water were mixed and stirred to completely dissolve. Under nitrogen protection, the sodium acrylate-acrylamide mixed solution, 6 kg of acrylonitrile and 1.25 kg of ammonium persulfate were added, and the mixture was reacted at 70°C and 300 rpm for 9 hours. After the reaction was completed, the mixture was cooled, freeze-dried, washed with anhydrous ethanol, and filtered to obtain a modified acrylic binder. 75 kg of deionized water was added to dissolve the mixture to obtain a 25 wt% modified acrylic binder.

[0045] Embodiment 5: A method for preparing a high-adhesion nano-coated copper current collector, specifically:

[0046] 10kg of conductive carbon black, 1kg of conductive graphite, 1kg of alumina, 40kg of 25wt% modified polyacrylic acid binder and 168kg of deionized water were mixed, 0.1kg of aziridine type crosslinking agent was added, and stirred evenly to obtain a nano coating slurry. The obtained nano coating slurry was coated on the surface modified copper current collector of cuprous iodide, and the coating thickness was 1μm, so as to obtain a high adhesion nano coating copper current collector.

[0047] Wherein, the preparation method of the cuprous iodide surface-modified copper current collector is:

[0048] The 6 μm copper current collector was washed with ethanol and deionized water to remove dust and impurities on the surface and dried at room temperature to obtain a pretreated copper current collector.

[0049] 15 kg of copper sulfate pentahydrate and 100 kg of deionized water were mixed and stirred evenly, 0.3 kg of 1-butyl-3-methyl-imidazole iodide was added, and ultrasonic dispersion was performed to form a mixed solution. The pretreated copper current collector was placed in the mixed solution and immersed at room temperature for 10 minutes. After the immersion was completed, it was taken out, washed with deionized water, and dried to obtain a copper current collector with a surface modified by cuprous iodide.

[0050] The preparation method of the modified acrylic acid adhesive is:

[0051] 8.5 kg of sodium hydroxide and 42.5 kg of deionized water were mixed and stirred to obtain a sodium hydroxide solution. At 5°C, 15 kg of acrylic acid was mixed with the sodium hydroxide solution to obtain a sodium acrylate solution. 4 kg of acrylamide was added to the sodium acrylate solution and stirred to obtain a sodium acrylate-acrylamide mixed solution. 0.75 kg of methyl allyl polyoxyethylene ether and 20 kg of deionized water were mixed and stirred to completely dissolve. Under nitrogen protection, the sodium acrylate-acrylamide mixed solution, 6 kg of acrylonitrile and 1.25 kg of ammonium persulfate were added, and the mixture was reacted at 70°C and 300 rpm for 9 hours. After the reaction was completed, the mixture was cooled, freeze-dried, washed with anhydrous ethanol, and filtered to obtain a modified acrylic binder. 75 kg of deionized water was added to dissolve the mixture to obtain a 25 wt% modified acrylic binder.

[0052] Embodiment 6: A method for preparing a high-adhesion nano-coated copper current collector, specifically:

[0053] 10 kg of conductive carbon black, 1 kg of conductive graphite, 1 kg of alumina, 40 kg of polydopamine-modified polyacrylic acid binder and 168 kg of deionized water were mixed, 0.1 kg of aziridine-type cross-linking agent was added, and stirred evenly to obtain a nano-coating slurry. The obtained nano-coating slurry was coated on a 6 μm copper current collector with a coating thickness of 1 μm to obtain a high-adhesion nano-coated copper current collector.

[0054] Wherein, the preparation method of the cuprous bromide surface modified copper current collector is:

[0055] The 6 μm copper current collector was washed with ethanol and deionized water to remove dust and impurities on the surface and dried at room temperature to obtain a pretreated copper current collector.

[0056] 15 kg of copper sulfate pentahydrate and 100 kg of deionized water were mixed and stirred evenly, 0.46 kg of dodecyltrimethylammonium bromide was added, and ultrasonic dispersion was performed to form a mixed solution. The pretreated copper current collector was placed in the mixed solution and immersed at room temperature for 10 minutes. After the immersion was completed, it was taken out, washed with deionized water, and dried to obtain a copper bromide surface-modified copper current collector.

[0057] The preparation method of the polydopamine-modified polyacrylic acid binder is:

[0058] 8.5 kg of sodium hydroxide and 42.5 kg of deionized water were mixed and stirred to obtain a sodium hydroxide solution. At 5°C, 15 kg of acrylic acid was mixed with the sodium hydroxide solution to obtain a sodium acrylate solution. 4 kg of acrylamide was added to the sodium acrylate solution and stirred to obtain a sodium acrylate-acrylamide mixed solution. 0.75 kg of methyl allyl polyoxyethylene ether and 20 kg of deionized water were mixed and stirred to completely dissolve. Under nitrogen protection, the sodium acrylate-acrylamide mixed solution, 6 kg of acrylonitrile and 1.25 kg of ammonium persulfate were added, and the mixture was reacted at 70°C and 300 rpm for 9 hours. After the reaction was completed, the mixture was cooled, freeze-dried, washed with anhydrous ethanol, and filtered to obtain a modified acrylic binder. 75 kg of deionized water was added to dissolve the mixture to obtain a 25 wt% modified acrylic binder.

[0059] 0.5 kg of dopamine was mixed with 9.5 kg of tris(hydroxymethyl)aminomethane hydrochloric acid buffer solution, and stirred at room temperature for 8 hours to obtain a polydopamine solution. The polydopamine solution was mixed with 30 kg of 25 wt% modified acrylic acid binder, and stirred evenly to obtain a polydopamine-modified polyacrylic acid binder.

[0060] Embodiment 7: A method for preparing a high-adhesion nano-coated copper current collector, specifically:

[0061] 10 kg of conductive carbon black, 1 kg of conductive graphite, 1 kg of alumina, 40 kg of polydopamine-modified polyacrylic acid binder and 168 kg of deionized water were mixed, 0.1 kg of aziridine-type cross-linking agent was added, and stirred evenly to obtain a nano-coating slurry. The obtained nano-coating slurry was coated on a 6 μm copper current collector with a coating thickness of 1 μm to obtain a high-adhesion nano-coated copper current collector.

[0062] Wherein, the preparation method of the cuprous iodide surface-modified copper current collector is:

[0063] The 6 μm copper current collector was washed with ethanol and deionized water to remove dust and impurities on the surface and dried at room temperature to obtain a pretreated copper current collector.

[0064] 15 kg of copper sulfate pentahydrate and 100 kg of deionized water were mixed and stirred evenly, 0.3 kg of 1-butyl-3-methyl-imidazole iodide was added, and ultrasonic dispersion was performed to form a mixed solution. The pretreated copper current collector was placed in the mixed solution and immersed at room temperature for 10 minutes. After the immersion was completed, it was taken out, washed with deionized water, and dried to obtain a copper current collector with a surface modified by cuprous iodide.

[0065] The preparation method of the polydopamine-modified polyacrylic acid binder is:

[0066] 8.5 kg of sodium hydroxide and 42.5 kg of deionized water were mixed and stirred to obtain a sodium hydroxide solution. At 5°C, 15 kg of acrylic acid was mixed with the sodium hydroxide solution to obtain a sodium acrylate solution. 4 kg of acrylamide was added to the sodium acrylate solution and stirred to obtain a sodium acrylate-acrylamide mixed solution. 0.75 kg of methyl allyl polyoxyethylene ether and 20 kg of deionized water were mixed and stirred to completely dissolve. Under nitrogen protection, the sodium acrylate-acrylamide mixed solution, 6 kg of acrylonitrile and 1.25 kg of ammonium persulfate were added, and the mixture was reacted at 70°C and 300 rpm for 9 hours. After the reaction was completed, the mixture was cooled, freeze-dried, washed with anhydrous ethanol, and filtered to obtain a modified acrylic binder. 75 kg of deionized water was added to dissolve the mixture to obtain a 25 wt% modified acrylic binder.

[0067] 0.5 kg of dopamine was mixed with 9.5 kg of tris(hydroxymethyl)aminomethane hydrochloric acid buffer solution, and stirred at room temperature for 8 hours to obtain a polydopamine solution. The polydopamine solution was mixed with 30 kg of 25 wt% modified acrylic acid binder, and stirred evenly to obtain a polydopamine-modified polyacrylic acid binder.

[0068] The following are comparative experiments based on Example 1, specifically Comparative Example 1 and Comparative Example 2, as described below:

[0069] Comparative Example 1: This comparative example relates to a method for preparing a high-adhesion nano-coated copper current collector, and the only difference from Example 1 is that no anchoring agent aluminum oxide is added to the nano-coating slurry. Specifically:

[0070] 10kg of conductive carbon black, 1kg of conductive graphite, 40kg of 25wt% modified polyacrylic acid binder and 168kg of deionized water were mixed, 0.1kg of aziridine type crosslinking agent was added, and stirred evenly to obtain a nano-coating slurry. The obtained nano-coating slurry was coated on a 6μm copper current collector with a coating thickness of 1μm to obtain a high-adhesion nano-coating copper current collector.

[0071] Comparative Example 2: This comparative example relates to a method for preparing a high-adhesion nano-coated copper current collector, which differs from Example 1 only in that no aziridine-type crosslinking agent is added to the nano-coating slurry. Specifically:

[0072] 10kg of conductive carbon black, 1kg of conductive graphite, 1kg of alumina, 40kg of 25wt% modified polyacrylic acid binder and 168kg of deionized water were mixed and stirred evenly to obtain a nano-coating slurry. The obtained nano-coating slurry was coated on a 6μm copper current collector with a coating thickness of 1μm to obtain a high-adhesion nano-coating copper current collector.

[0073] Comparative Example 3: This comparative example relates to a method for preparing a high-adhesion nano-coated copper current collector, which differs from Example 1 only in that a polyacrylic acid binder is used in the nano-coating slurry. Specifically:

[0074] 10kg of conductive carbon black, 1kg of conductive graphite, 1kg of alumina, 40kg of 25wt% polyacrylic acid binder and 168kg of deionized water were mixed, 0.1kg of aziridine type crosslinking agent was added, and stirred evenly to obtain a nano-coating slurry. The obtained nano-coating slurry was coated on a 6μm copper current collector with a coating thickness of 1μm to obtain a high-adhesion nano-coating copper current collector.

[0075] Detection experiment:

[0076] According to the processes in Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Comparative Example 1, Comparative Example 2, and Comparative Example 3, a high adhesion nano-coated copper current collector was prepared, and a 6 μm copper current collector not coated with nano-coating slurry was used as Comparative Example 4 for testing.

[0077] Peel strength test:

[0078] The 10 prepared high-adhesion nano-coated copper current collectors and the 6μm copper current collector without nano-coating slurry were coated with 90μm thick negative electrode materials respectively and dried. A 20mm wide and 200mm long specimen was taken from the center of the electrode sheet, and a 20mm wide 3M tape was taken and bonded to the center of a 50mm×100mm steel plate. The specimen was aligned with one end of the tape and fitted together. At the other end, the specimen was reversed 180° and installed at a certain distance on the lower chuck of the universal material testing machine. The reverse end of the specimen was then installed on the upper chuck of the universal material testing machine. The specimen was started to be pulled, and the tensile speed was set to 100mm / min until the specimen was detached from the tape. The test was stopped and the peel strength of the specimen was recorded.

[0079] After the sample is rolled (negative electrode material compaction density: 1.4g / cm 3 ), and measure again using the above method.

[0080]

[0081] Conclusion: According to the test data, it can be seen that before and after rolling, the peel strength of the high adhesion nano-coated copper current collector prepared by the preparation method of Example 1 is better than that of Comparative Example 1, Comparative Example 2, and Comparative Example 3, and after rolling, the peel strength of the copper current collector with a high adhesion nano-coating is further enhanced.

[0082] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A high-adhesion nano-coated copper current collector, characterized in that: The invention comprises a copper current collector and a nano coating coated on the surface of the copper current collector. The dosage of each component in the nano coating is: 6 to 22 parts of a conductive agent, 0.05 to 4 parts of an anchoring agent, 0.5 to 1.5 parts of a modified polyacrylic acid binder, and 0.01 to 0.1 parts of a cross-linking agent.

2. A high adhesion nano-coated copper current collector according to claim 1, characterized in that: The conductive agent includes conductive agent A and conductive agent B, conductive agent A is at least one of conductive carbon black and carbon nanotubes, conductive agent B is at least one of conductive graphite and graphene, the particle size of conductive agent B is 1 to 2 μm, and the mass ratio of conductive agent A to conductive agent B is (5 to 10):

1.

3. The high adhesion nano-coated copper current collector according to claim 1, characterized in that: The crosslinking agent is at least one of isocyanate, aziridine type curing agent and epoxy type curing crosslinking agent; the anchoring agent is at least one of alumina ceramic particles and boehmite.

4. The high-adhesion nano-coated copper current collector according to claim 1, characterized in that: The specific preparation steps of the modified polyacrylic acid binder are: Mix sodium hydroxide and deionized water, stir evenly to obtain a sodium hydroxide solution, mix acrylic acid with the sodium hydroxide solution at 0-10°C to obtain a sodium acrylate solution, add acrylamide to the sodium acrylate solution, stir evenly to obtain a sodium acrylate-acrylamide mixed solution, mix methyl allyl polyoxyethylene ether and deionized water, stir evenly to completely dissolve them, add the sodium acrylate-acrylamide mixed solution, acrylonitrile and ammonium persulfate under nitrogen protection, react at 65-75°C and 250-350rpm for 8-10h, cool after the reaction is completed, freeze-dry, wash with anhydrous ethanol, filter and obtain a modified polyacrylic acid binder.

5. A method for preparing a high-adhesion nano-coated copper current collector, characterized in that: The preparation method is: Conductive agent A, conductive agent B, anchoring agent, modified polyacrylic acid binder and deionized water are mixed, a crosslinking agent is added, and the mixture is stirred evenly to obtain a nano coating slurry, and the nano coating slurry is coated on a copper current collector to obtain a high-adhesion nano coating copper current collector.

6. The high-adhesion nano-coated copper current collector according to claim 1, characterized in that: The copper current collector is a copper bromide surface-modified copper current collector, and the preparation method is as follows: The copper current collector is washed with ethanol and deionized water to remove dust and impurities on the surface, and dried at room temperature to obtain a pretreated copper current collector. Copper sulfate pentahydrate and deionized water are mixed and stirred evenly. Dodecyltrimethylammonium bromide is added and ultrasonically dispersed to form a mixed solution. The pretreated copper current collector is placed in the mixed solution and immersed at room temperature for 5 to 20 minutes. After the immersion is completed, it is taken out, washed with deionized water, and dried to obtain a copper current collector with a cuprous bromide surface modification.

7. The high-adhesion nano-coated copper current collector according to claim 1, characterized in that: The copper current collector is a copper current collector surface-modified with cuprous iodide, and the preparation method is as follows: The copper current collector is washed with ethanol and deionized water to remove dust and impurities on the surface, and dried at room temperature to obtain a pretreated copper current collector. Copper sulfate pentahydrate and deionized water are mixed and stirred evenly. 1-butyl-3-methylimidazole iodide is added and ultrasonically dispersed to form a mixed solution. The pretreated copper current collector is placed in the mixed solution and immersed at room temperature for 5 to 20 minutes. After the immersion is completed, it is taken out, washed with deionized water, and dried to obtain a cuprous iodide surface-modified current collector.

8. The high-adhesion nano-coated copper current collector according to claim 1, characterized in that: The modified polyacrylic acid binder is a polydopamine-modified polyacrylic acid binder, and the preparation method is as follows: Dopamine is mixed with tris(hydroxymethyl)aminomethane hydrochloric acid buffer solution, and stirred at room temperature for 6 to 10 hours to obtain a polydopamine solution. The polydopamine solution and a modified polyacrylic acid binder are evenly mixed to obtain a polydopamine-modified polyacrylic acid binder.

9. Use of the high-bonding nano-coating current collector according to any one of claims 1 to 4 in negative electrode materials of lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of high-rate carbon-coated aluminum foil current collector for lithium battery

    CN117059819A

  • Negative pole piece, preparation method thereof and battery

    CN117913212A

  • Current collector for improving initial charge-discharge efficiency and pole piece stripping force of lithium battery

    CN118825277A

  • Electrode sheet and electrochemical device

    WO2023093503A1

  • Electrode sheet and electrochemical device

    WO2023093506A1